1991
DOI: 10.1111/j.1528-1157.1991.tb05608.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflex Epilepsy Induced by Calculation Using a “Soroban,” a Japanese Traditional Calculator

Abstract: We report three cases of reflex epilepsy with myoclonic jerks of the right arm and fingers precipitated by calculation using a Soroban. An EEG spike-wave complex with left central prevalence was induced. Various types of stimulation were used to induce epileptic discharges, and a simultaneous mental task requiring a high degree of concentration and complicated and delicate finger movements was necessary to induce the epileptic discharges. Comparison of our cases with previously reported reflex epilepsy induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Their clinical characteristics were very similar to those of our patients (Table 2). These differences may not be attributable to differences in the ethnicity between the Asian and Western patients studied, since the clinical features of patients observed in the Japanese literature13,14 are quite similar to those observed by the Andermann group. Although the triggering stimuli have differed somewhat between studies, it is also unlikely that this factor is responsible for the differences in the clinical profiles between groups.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Their clinical characteristics were very similar to those of our patients (Table 2). These differences may not be attributable to differences in the ethnicity between the Asian and Western patients studied, since the clinical features of patients observed in the Japanese literature13,14 are quite similar to those observed by the Andermann group. Although the triggering stimuli have differed somewhat between studies, it is also unlikely that this factor is responsible for the differences in the clinical profiles between groups.…”
Section: Discussionsupporting
confidence: 50%
“…They suggested that this form of reflex epilepsy might be a rather homogeneous syndrome with the clinical and EEG characteristics of IGE 9-11. This suggestion has been supported by Inoue et al13and Yamamoto et al14…”
Section: Discussionmentioning
confidence: 55%
“…The term was first used by Daniele et al 1 but there is an earlier literature presenting specific aspects of PI such as playing chess, card or other games, 2-5 calculations, 6,7 writing, 8,9 drawing 10 and decision making. 11 Inoue et al 12 reviewed the literature and proposed to consider PI as a common denominator.…”
Section: History and Delineationmentioning
confidence: 99%
“…(Gastaut and Broughton, 1972;Kawai and Fujii, 1979). Seizures triggered by a particular mental activity have also been described, including reading , writing (Symonds, 1959), drawing (Brenner and Seelinger, 1979) and mathematical calculations, spatial tasks, and complex decision making (Ingvar and Nyman, 1962;Wilkins et al, 1982;Goossens et al, 1990;Yamamoto et al, 1991). With the exception of reading epilepsy, in which both photo and pattern sensitivity may exist (Gastaut and Broughton, 1972), these seizures may be provoked by psychic elaboration of the perceived sensory data rather than the simple sensations (Goosens et al, 1990).…”
Section: Precipitation Of Seizures By Particular Stimulimentioning
confidence: 99%